Molecular phenotypes of acute rejection predict kidney graft prognosis - Viklicky, Ondrej; Hribova, Petra; Volk, Hans-Dieter; Slatinska, Janka; Petrasek, Jan; Bandur, Stepan; Honsova, Eva; Reinke, Petra (Journal of the American Society of Nephrology, 2010)
Earlier detection of antibody-mediated rejection of kidney allografts may improve graft outcomes. Profiling of gene expression holds promise for the diagnosis and prognosis of antibody-mediated rejection. Here, we identified 730 patients who received kidney transplants during 2002-2005, including 21 patients (2.9%) who experienced early acute antibody-mediated rejection. We also identified a matched group of 43 patients with early acute T cell-mediated rejection to serve as controls. Compared with patients with T cell-mediated rejection, those with antibody-mediated rejection had significantly higher intrarenal mRNA expression of the cytoprotective heme oxygenase-1 but had lower expression of the regulatory T cell marker forkhead box P3 (FoxP3), the B cell marker CD20, and the chemokine regulated upon activation, normal T cell expressed and secreted (RANTES). T cell infiltration was similar in both groups of patients. Compared with grafts that had a favorable course, those that failed as a result of antibody-mediated rejection had expression profiles suggesting a lack of regulation (less FoxP3, TGF-beta1, RANTES, and CD20). Grafts that failed as a result of T cell-mediated rejection only revealed lower expression of CD20 mRNA. In summary, these data suggest that severe antibody-mediated rejection and T cell-mediated rejection result in graft loss by distinct mechanisms. Molecular phenotypes of early acute rejection might help to identify grafts with poor prognosis, allowing earlier application of additional therapies.
Keywords: antigeny CD20; protilátky; fenotyp; Male; Phenotype; retrospektivní studie; forkhead transkripční faktory; Risk Factors; Antigens, CD20; prognóza; Kaplan-Meier Estimate; Adult; Kaplanův-Meierův odhad; Case-Control Studies; dospělí; Forkhead Transcription Factors; mužské pohlaví; transformující růstový faktor beta1; Graft Rejection; stanovení celkové genové exprese; chemokin CCL5; T-lymfocyty; Chemokine CCL5; Gene Expression Profiling; Transforming Growth Factor beta1; Antibodies; lidé; ženské pohlaví; studie případů a kontrol; Kidney Transplantation; transplantace ledvin; Humans; rejekce štěpu; rizikové faktory; prediktivní hodnota testů; Prognosis; T-Lymphocytes; Retrospective Studies; Female; lidé středního věku; Predictive Value of Tests; Middle Aged